2018
DOI: 10.3390/pr6070091
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimal Design of Absorbent Enhanced Ammonia Synthesis

Abstract: Synthetic ammonia produced from fossil fuels is essential for agriculture. However, the emissions-intensive nature of the Haber-Bosch process, as well as a depleting supply of these fossil fuels have motivated the production of ammonia using renewable sources of energy. Small-scale, distributed processes may better enable the use of renewables, but also result in a loss of economies of scale, so the high capital cost of the Haber-Bosch process may inhibit this paradigm shift. A process that operates at lower p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 20 publications
(36 reference statements)
1
59
0
Order By: Relevance
“…The tests performed revealed that the proposed mathematical model for the industrial reactor using carbon dioxide absorption in diethanolamine activated potassium carbonate solutions leads to a calculation error of up to maximum 4%, in accordance with literature [43][44][45][46].…”
Section: Testing the Mathematical Model Of The Reactor Under Isobar-isupporting
confidence: 85%
“…The tests performed revealed that the proposed mathematical model for the industrial reactor using carbon dioxide absorption in diethanolamine activated potassium carbonate solutions leads to a calculation error of up to maximum 4%, in accordance with literature [43][44][45][46].…”
Section: Testing the Mathematical Model Of The Reactor Under Isobar-isupporting
confidence: 85%
“…This is a unique property in comparison to magnesium chloride (MgCl 2 ) and calcium chloride (CaCl 2 ), conventional absorbents for ammonia separation due to their plentifulness. [ 5,29–31 ] CaCl 2 does not absorb ammonia at reasonable ammonia partial pressures above 300 °C and therefore is not suitable for a combined catalyst‐absorbent process. [ 32 ] While MgCl 2 is known to retain ammonia up to almost 400 °C, its implementation is severely hindered by its decomposition which releases hydrogen chloride.…”
Section: Resultsmentioning
confidence: 99%
“…The interesting possibility of extending the favorable characteristics of cuboid packed-bed devices originally designed for chromatographic separations to packed-bed chemical reactors is explored in the third paper [3]. The fourth paper addresses the optimal design of ammonia production plants based on adsorption for unreacted nitrogen and hydrogen recovery and wind energy for electricity generation [4].…”
Section: Chemical Processesmentioning
confidence: 99%